AGEs, macrophage colony stimulating factor and vascular adhesion molecule blood levels are increased in patients with diabetic microangiopathy - Wautier, Marie-Paule; Boulanger, Eric; Guillausseau, Pierre-Jean; Massin, Pascale; Wautier, Jean-Luc (Thrombosis and Haemostasis, 2004)
In vitro experiments and animal models indicate that advanced glycation end products (AGEs) may play a crucial role in the vascular dysfunctions observed in patients with diabetes mellitus. These results prompted us to study subrogate markers of inflammation or vascular dysfunction in type II diabetic patients. Monocyte count and activation are dependent upon macrophage colony stimulating factors (M-CSF). Soluble vascular cell adhesion molecule (sVCAM-1) blood levels have been proposed as a marker for endothelium activation. To explore a possible relationship between these factors in diabetic patients, we measured a chemically defined AGE, N(carboxymethyl)lysineprotein (CML-protein) in a group of normal subjects (n = 55) and of diabetic patients (n = 40) using ELISA. Simultaneously, we determined M-CSF and sVCAM-1 blood levels. We found that CML-protein blood levels were significantly higher in patients with diabetes compared to non-diabetic subjects (40.2 ± 4.7 and 7.9 ± 0.7 pmol/mg protein respectively, p < 0.0001). M-CSF was increased while sVCAM-1 blood levels were normal in the group of diabetics. M-CSF blood level was correlated to CML-protein blood level (p < 0.05). In addition CML-protein, M-CSF and sVCAM-1 were increased in patients with microangiopathy. These results suggest that AGE may contribute to vascular dysfunction including microangiopathy.
Keywords: Advanced glycation end products; carboxymethyl-lysine; macrophage colony stimulating factor and adhesion molecules